2014
DOI: 10.4067/s0717-92002014000200011
|View full text |Cite
|
Sign up to set email alerts
|

Hongos endófitos antárticos como herramienta para la reintroducción de especies nativas en zonas áridas

Abstract: SUMMARYEcological restoration is the deliberate action that speeds recovery from a degraded system by direct or indirect human intervention. Xerophytic formations are among the most degraded ecosystems where low water availability makes reintroduction plans unsuccessful and extremely expensive. Roots inoculation with endophytic fungi has been reported as a successful strategy to maintain or improve the ecophysiological performance and survival in different species of shrubs and trees. In harsh environments, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Fardella et al (2014) suggest that one of the endophytic fungal species that they introduced might increase plant growth and survival by reducing insect herbivory on roots. By providing protection only to some plants, introduced endophytes will change the competitive hierarchies of plants (Omacini 2014).…”
Section: Can Nonnative Mutualists Be a Problem?mentioning
confidence: 99%
See 4 more Smart Citations
“…Fardella et al (2014) suggest that one of the endophytic fungal species that they introduced might increase plant growth and survival by reducing insect herbivory on roots. By providing protection only to some plants, introduced endophytes will change the competitive hierarchies of plants (Omacini 2014).…”
Section: Can Nonnative Mutualists Be a Problem?mentioning
confidence: 99%
“…Fardella et al (2014) have found that the addition of root-associated Antarctic endophytic fungi can have positive effects by increasing or maintaining survivorship in three native plant species, facilitating establishment of native plants and restoration efforts in extreme climatic habitats. However, despite these benefits, we need to consider that the potential problems may far exceed the benefits of these new introductions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations